Pengaruh Penambahan Serat Asbes Terhadap Sifat Refractory Brick Berbahan Kaolin dan Fly Ash - Handoko, Dwi; Azmal, Azmal; Iyus, Iyus (Politeknik Negeri Pontianak, 2024)
Abstract: This study aims to determine the effect of adding asbestos to the production of refractory bricks with different material compositions, namely kaolin, fly ash, asbestos and standard water. The composition of kaolin and fly ash is given in equal percentages, varying according to the mass of asbestos, 0 (%), 10 (%), 15 (%), 20 (%), 30 (%). The tests carried out are thermal conductivity and mechanical properties, where these results become parameters for determining the best composition. The results of testing the compressive strength of refractory bricks showed that 0 (%) quartz sand composition had the largest compressive strength, namely 14.40 (Mpa), the impact test results for 0 (%) asbestos fiber composition had the largest value, namely 0.084 (Joule/mm2), while the results Heat conductivity testing showed that quartz composition 30 (%) had the lowest value, namely 0.373 K(W/mC), thus the addition of asbestos fiber can reduce heat conductivity but cause a decrease in the compressive and impact mechanical properties of refractory bricks. Keywords: Refractory bricks, refractories, kaolin, fly ash, asbestos